PENGARUH MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS V SD - Nia Gemala Putri Rizal, Syaiva; Anitra, Rien; Basith, Abd. (EMTEKA: Jurnal Pendidikan Matematika, 2024)
The focus of this study is to ascertain the differences, also how much influence the TAI learning model has on students' mathematical creative thinking skills on pictogram material in class V of SDN 86 Singkawang. The study is quantitative in nature and utilizes a posttest-only control group design, which is a true experimental design. The population of this study was all students of class V of SDN 86 Singkawang totaling 46 students. The sampling technique was purposive sampling, the sample in this study were students of class VB as the experimental class, also VA as the control class. The data collection technique was a measurement technique with a post-test question sheet for mathematical creative thinking skills. The data analysis technique was the T-Test & Effect Size. The outcomes of the study were: 1) there was a difference in mathematical creative thinking skills between students who received the TAI learning model and students who applied the direct learning model to the pictogram material in class V of SDN 86 Singkawang. 2) the TAI learning model had a high impacy on students' mathematical creative thinking skills on the pictogram material in class V of SDN 86 Singkawang with a value of 0.91. From the research outcomes, it was inferred that the TAI learning model has a significant impact on the mathematical creative thinking abilities of class V students at SDN 86 Singkawang.